2005
DOI: 10.1093/icb/45.1.72
|View full text |Cite
|
Sign up to set email alerts
|

The Freshwater Mussel (Elliptio complanata) as a Sentinel Species: Vitellogenin and Steroid Receptors

Abstract: Freshwater mussels, Elliptio complanata were collected from a reference and pollutant-impacted pond on Cape Cod, MA. Glutathione-S-transferase (GST) activity was measured in gill, hepatopancreas and foot. In addition, content of seven heavy metals were measured in whole bodies. GST activity was significantly elevated in hepatopancreas and foot, as was whole body cadmium level in animals from the contaminated site suggesting that these animals have been exposed to organic and inorganic contaminants. Sodium dode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Corroborating the results of Dorange and Le Pennec (1989), who found ER-like immuno-reactivity in the nuclei of oocytes and auxiliary cells of Pecten maximus, Osada et al (2003) revealed ER immuno-reactivity in the growing oocytes and auxiliary cells of the scallop, P. yessoensis, to be co-localized with vitellin. Using immuno-blotting techniques, Stefano et al (2003a) found an ERb-like protein in the pedal ganglia of M. edulis, Canesi et al (2004) reported on the discovery of ERa and ERb in haemocyte protein extracts of Mytilus galloprovincialis, and Won et al (2005) found an ERb-like protein in the female foot and ovary of E. complanata, while hepatopancreatic protein exracts failed to show crossreactivity. On the molecular level, Stefano et al (2003b) recently isolated a 266 bp fragment from the pedal ganglia of M. edulis with 100% identity to the human ERb gene.…”
Section: Molluscamentioning
confidence: 99%
“…Corroborating the results of Dorange and Le Pennec (1989), who found ER-like immuno-reactivity in the nuclei of oocytes and auxiliary cells of Pecten maximus, Osada et al (2003) revealed ER immuno-reactivity in the growing oocytes and auxiliary cells of the scallop, P. yessoensis, to be co-localized with vitellin. Using immuno-blotting techniques, Stefano et al (2003a) found an ERb-like protein in the pedal ganglia of M. edulis, Canesi et al (2004) reported on the discovery of ERa and ERb in haemocyte protein extracts of Mytilus galloprovincialis, and Won et al (2005) found an ERb-like protein in the female foot and ovary of E. complanata, while hepatopancreatic protein exracts failed to show crossreactivity. On the molecular level, Stefano et al (2003b) recently isolated a 266 bp fragment from the pedal ganglia of M. edulis with 100% identity to the human ERb gene.…”
Section: Molluscamentioning
confidence: 99%
“…Nonetheless, E. complanata and most Unionid bivalves are predominantly dioecious, and this is particularly so for larger animals (Kat, 1983). E. complanata , has long been used for in situ testing of estrogenic pollutants in studies focusing on physiological endpoints, such as shell growth, tissue weight and expression of the egg yolk protein precursor, vitellogenin (VTG) in males (Gagné et al, 2001; Gagné and Blaise, 2003; Won et al, 2005). Behavioral endpoints have been tested in other bivalve species: inhibition of valve gaping in swan mussels ( Anodonta cygnea ) and burrowing in little neck clams ( Protothaca staminea ) following metal pollution (Kadar et al, 2001; Phelps et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Köhler et al (2007) (Canesi et al, 2004;Di Cosmo et al, 2002;Dorange and Le Pennec, 1989;Osada et al, 2003;Stefano et al, 2003;Won et al, 2005). However, the ability of antibodies to react with similar antigenic sites on different proteins (antibody cross reactivity) must be seen as a disadvantage of immunochemical assays and clearly reduces the usefulness of these methods to demonstrate steroid receptor presence unless the antibodies have been directed specifically at the mollusc receptors themselves.…”
Section: (Neuro-)endocrine Control In Molluscsmentioning
confidence: 99%